Pathological Changes of Urinary System in a Dog with Urolithiasis and Renal Papillary Necrosis - Kutlu, Tuncer; Yücel-Tenekeci, Gözde; Pekcan, Mert; Yengy Kuler, Emir; Kutsal, Osman (Acta Scientiae Veterinariae, 2019)
Background: Urolithiasis is one of the important lower urinary tract diseases in dogs. Uroliths develop when urine becomes "supersaturated”. Struvite urolithiasis in dogs is formed when urine saturated with magnesium, ammonium and phosphate. Renal papillary necrosis is a form of nephropathy involving the necrosis of the renal papilla. The aim of this case is the evaluation of histopathological changes in kidney and urinary bladder caused by urolithiasis with sitruvite, a pathology commonly seen in dogs. Renal papillary necrosis that encountered in the case was evaluated histopathologically. We intend to discuss the relationship between urolithiasis and renal papillary necrosis. Case: The material of the case was a 7.5 year-old Rottweiler female dog that had been operated for the urolithiasis treatment and died after surgery. The animal sent to pathology department was necropsied and evaluated histopathologically. Also the uroliths removed during the surgery were sent for analysis postoperatively. Qualitative composition of uroliths was determined by a series of chemical analyses in Department of Biochemistry. X-ray diffraction was performed as well in General Directorate of Mineral Research and Exploration in the objective of result verification. Macroscopically, 30 pieces uroliths with varying size from 1 mm to 3 cm were seen in urinary bladder. They were 110 g in weight with smooth surface and round and/or ovoid shapes. After necropsy, specimens from kidney and urinary bladder were fixed in 10% neutral buffered formalin, embedded in paraffin wax, cut at 5 μm, and stained with hematoxylin and eosin (HE). Bladder wall thickening and hemorrhage on mucosa were noticed. Kidneys had roughened surface with the capsule being difficult to peel off. Also, renal papillary necrosis, reddish in color was observed in papilla of the right kidney. Microscopically, crystal formations were observed proximal tubule lumens of kidneys. Interstitial nephritis in cortex and medulla had been noticed in both kidneys. Interstitial nephritis has been noticed in both kidneys. Hemorrhagic necrotic area demarcated by connective tissue was encountered in medulla of the right kidney. In the lamina propria of urinary bladder hemorrhage were noted. Desquamation and degeneration of lamina epithelialis and wide hemorrhage area in lamina propria were noted in urinary bladder. Results obtained from biochemical analysis were verified with x-ray diffraction method, uroliths were determined as magnesium ammonium phosphate (struvite). Discussion: Renal papillary necrosis is a form of nephropathy involving the necrosis of the renal papilla, caused by ischemia of the inner medulla of the kidney. According to the first report of renal papillary necrosis, symmetrical soft calyceal concretions and their appearances are typical lesions for diagnosis of renal papillary necrosis. The presence of crystals in the tubule lumen and the formation of struvite stone (which has the same chemical composition with calyceal concretions) established a distinct relationship between urolithiasis and renal papillary necrosis. This case showed that struvite stones can reach large volumes in urinary bladder, and caused bladder wall thickness and hemorrhages. Also, the lower urinary tract obstruction or urolithiasis should be remembered in the renal papillary necrosis together with the risk of hydronephrosis.